Benchmarking smart e-government development: insight from a national perspective - Máchová, Renáta; Komárková, Jitka; Kopáčková, Hana; Lněnička, Martina (Univerzita Pardubice, 2018)
The concept of smartness has become a priority area for many governments, driven by the effort to enhance their ability to provide more attractive and user-focused public services. This approach has also influence on the set of indicators that are used to evaluate these efforts. In contrast to the previous studies to benchmark e-government development, the society is now more advanced in using ICT and consuming online public services. There is a need to reshape traditional view on e-government development and introduce a new set of indicators that would better capture the full range of smarter e-government. This paper provides insights on this issue from a national perspective. A two-step validation process was applied to evaluate the capabilities of the new set of indicators to assess and benchmark smart e-government development. The results indicate that the newly proposed index provides a robust measure to benchmark smart e-government development.
Keywords: e-government development; smartness; expert panel; benchmarking framework; composite index; C43; H11; H83; L86